Implementasi Regresi Linear Berganda Prediksi Faktor-faktor Indeks Pembangunan Manusia di Provinsi Jawa Barat - Riza, Noviana; Maresti, Fatia Amalia; Azzahra, Siti Salwa; Ningsih, Salsa Paringga Pangestu (MASALIQ, 2025)
The Human Development Index (HDI) is a key indicator for measuring the welfare and prosperity of a region, including West Java Province. This study aims to analyze the factors influencing HDI and predict its future trends. The analysis was conducted using a multiple linear regression method implemented with the Python programming language, with independent variables including Life Expectancy, Expected Years of Schooling, Mean Years of Schooling, and Adjusted Per Capita Expenditure. The results show that Expected Years of Schooling (X3) and Adjusted Per Capita Expenditure (X4) are the most significant factors influencing HDI in West Java, particularly due to the declining trends in these variables. Based on the model, the predicted HDI values for 2024, 2025, and 2026 are 73.19, 72.59, and 71.62, respectively, which fall under the medium HDI category. These findings provide valuable insights for strategic planning to improve HDI in West Java, particularly through interventions targeting the significant variables.